2020
DOI: 10.1186/s13075-020-02327-4
|View full text |Cite
|
Sign up to set email alerts
|

Ectopic bone formation and systemic bone loss in a transmembrane TNF-driven model of human spondyloarthritis

Abstract: Background The transmembrane-TNF transgenic mouse, TgA86, has been shown to develop spontaneously peripheral arthritis with signs of axial involvement. To assess similarity to human spondyloarthritis, we performed detailed characterization of the axial, peripheral, and comorbid pathologies of this model. Methods TgA86 bone pathologies were assessed at different ages using CT imaging of the spine, tail vertebrae, and hind limbs and characterized in detail by histopathological and immunohistochemical analysis.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 38 publications
1
8
0
Order By: Relevance
“…These results confirm the findings of the studies on the transmembrane TNF (tmTNF) transgenic mouse model of SpA, in which it has been shown that the overexpression of tmTNF drives osteoproliferative joint inflammation seen in SpA. TNF receptor I signaling is essential for inflammation and TNF receptor II signaling contributes to pathological new bone formation [ 37 , 38 ]. Moreover, anti-TNF treatment with the etanercept in the same mouse model resulted in a reduction in axial and peripheral inflammation and a reduced bone surface roughness at the level of the caudal spine [ 38 ].…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…These results confirm the findings of the studies on the transmembrane TNF (tmTNF) transgenic mouse model of SpA, in which it has been shown that the overexpression of tmTNF drives osteoproliferative joint inflammation seen in SpA. TNF receptor I signaling is essential for inflammation and TNF receptor II signaling contributes to pathological new bone formation [ 37 , 38 ]. Moreover, anti-TNF treatment with the etanercept in the same mouse model resulted in a reduction in axial and peripheral inflammation and a reduced bone surface roughness at the level of the caudal spine [ 38 ].…”
Section: Discussionsupporting
confidence: 86%
“…TNF receptor I signaling is essential for inflammation and TNF receptor II signaling contributes to pathological new bone formation [ 37 , 38 ]. Moreover, anti-TNF treatment with the etanercept in the same mouse model resulted in a reduction in axial and peripheral inflammation and a reduced bone surface roughness at the level of the caudal spine [ 38 ]. In the clinic, TNF inhibitors are established in disease management of axSpA with efficacy in reducing inflammation [ 39 , 40 , 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…A series of recent studies using another preclinical mouse model of TNF overexpression have shed light on how the structure of TNF may contribute to SpA pathogenesis ( 52 , 67 ). The TgA86 mice systemically overexpress a mutant murine TNF gene that is defective at the ADAM17 cleavage site, thereby causing a specific increase of transmembrane-bound TNF (tmTNF) but not soluble TNF (sTNF) ( 68 ).…”
Section: New Data On the Link Between Inflammation And New Bone Formationmentioning
confidence: 99%
“…Indeed, it was found that stromal tmTNF overexpression could drive inflammation, especially at peripheral sites ( 52 ). Moreover, tmTNF-driven inflammation and bone erosion seemed to precede new bone formation, which involved both endochondral and membranous ossification ( 67 ). However, this model lacks extra-articular manifestations of the SpA disease spectrum, which suggests that additional triggers may be required to induce IBD, uveitis, and/or psoriasis in the background of increased susceptibility owing to the tmTNF-sTNF imbalance.…”
Section: New Data On the Link Between Inflammation And New Bone Formationmentioning
confidence: 99%
See 1 more Smart Citation